A comparison of two methods for determining titanium dioxide marker content in broiler digestibility studies. (11th February 2014) - Morgan, N. K.; Scholey, D. V.; Burton, E. J.
Abstract : The use of inert markers in broiler diets eliminates the need to quantitatively evaluate feed intake and excreta output to determine diet digestibility, and enables nutrient uptake at specific points along the gastrointestinal tract to be examined. Titanium dioxide (TiO2 ) is commonly used for this purpose and measured using a UV-spectrophotometric assay. Two experiments were conducted to observe whether an inductively coupled plasma optical emission spectrophotometer (ICP-OES) assay is able to replace the UV-spectroscopy assay for rapid analysis of TiO2 in broiler feed and ileal digesta samples. In the first experiment, TiO2 was added at 5 g/kg to 19 broiler diets. Ross 308 male broilers ( n =452) fed these diets were involved in a series of digestion studies to determine ileal digesta recovery of TiO2 . In the second experiment, defined amounts of TiO2 were added to ileal digesta samples from Ross 308 male broilers ( n =176) and TiO2 recoveries were determined. The feed and ileal samples from both experiments were analysed by both UV-spectroscopy and ICP-OES, and relatedness of the findings from the two assays was determined. Overall relatedness of the two assays was strong for determination of TiO2 concentration in both the broiler diets and ileal digesta samples ( r =0.908 and r =0.884, respectively). Overall recovery of supplemented TiO2 was 97.62% by the UV-spectroscopy assay and 98.77% by the ICP-OES assay. The ICP-OES assay in this study was as accurate as spectrophotometric determination for the quantification of TiO2 content. The ICP-OES method can also be used to analyse several elements within one assay, with a single preparation step, and thus the measurement of TiO2 may be incorporated into the analysis of other minerals. Time and resources dedicated to determining diet digestibility in broilers could be minimised by using the ICP-OES assay to replace the UV-spectroscopy assay when measuring TiO2 concentration.